Implementasi Model Pembelajaran Flipped Classroom Guna Meningkatkan Interaksi Belajar Mahasiswa pada Mata Kuliah Manajemen Informasi dan E-Administrasi - Thanthawi Ishak; Rudi Kurniawan; Zamzami Zainuddin (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2019)
This study aims to identify the effectiveness of student interaction in learning Information Management and E-Administration courses using the flipped classroom method. The theory of Moore (1989) and Hillman et al., (1994) was used in determining four models of student learning interactions both in class and outside the classroom. The four interactions include interactions between teaching participants (students), interactions between teaching participants and teachers, interactions between teaching participants and teaching materials and interactions between teaching participants and technology media. This research was conducted using a mixed methods research approach. Questionnaires and individual interviews were used to collect data. 29 of the teaching participants were given a questionnaire at the end of the semester and 10 of them were selected to be interviewed individually. The collected data were analyzed using descriptive statistics and data analysis using SPSS. The results of this study indicate that the teaching participants have positive perceptions in all components of the interaction in learning the Information Management and E-Administration courses using the flipped classroom method. The output of this research has contributed to a university in implementing innovative digital learning flipped classrooms using WhatsApp and YouTube media.